4th booster-dose SARS-CoV-2 heterologous and homologous vaccination in rheumatological patients - Gallardo-Nelson, Maria Jose; Cruces, Marcos; Gómez, Yolanda M.; Fuenzalida, Constanza; Silva, Javiera; Aravena-Traipi, Laura; Nuñez, Eduardo; Gaete-Angel, Aracelly; Rivas-Yañez, Elizabeth; Kalergis, Alexis M.; Soto-Rifo, Ricardo; Valiente-Echeverria, Fernando (Frontiers in Immunology, 2024)
Objective to evaluate the immune response to the SARS-CoV-2 vaccines in adults with immunemediated rheumatic diseases (IMRDs) in comparison to healthy individuals, observed 1-20 weeks following the fourth vaccine dose. Additionally, to evaluate the impact of immunosuppressive therapies, vaccination schedules, the time interval between vaccination and sample collection on the vaccine's immune response.We designed a longitudinal observational study conducted at the rheumatology department of Hospital de Copiapó. Neutralizing antibodies (Nabs) titers against the Wuhan and Omicron variant were analyzed between 1-20 weeks after administration of the fourth dose of the SARS-CoV-2 vaccine to 341 participants (218 IMRD patients and 123 healthy controls). 218 IMRD patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS), systemic lupus erythematosus (SLE), systemic vasculitis (VS) and systemic scleroderma (SS) were analyzed.